Pregnant women's knowledge of birth defects and their associated factors among antenatal care attendees in referral hospitals of Amhara regional state, Ethiopia, in 2019 - Ferede, Addisu Andualem; Kassie, Belayneh Ayanaw; Mosu, Kiber Temesgen; Getahun, Worku Taye; Taye, Birhan Tsegaw; Desta, Melaku; Fetene, Mamaru Getie (Frontiers in Global Women's Health, 2023)
Birth defects (BDs) are structural, behavioral, functional, and metabolic disorders present at birth. Due to a lack of knowledge, families and communities stigmatized pregnant women following the birth of a child with birth defects. In Ethiopia, there was limited evidence to assess the level of knowledge among pregnant women despite increasing magnitude of birth defects.To assess pregnant women's knowledge of birth defects and its associated factors among antenatal care attendees in referral hospitals of Amhara regional state, 2019.From June 1 to June 30, 2019, 636 pregnant women receiving prenatal care participated in an institution-based cross-sectional study. The approach for sampling was multistage. A semistructured pretested interviewer-administered questionnaire was used to collect data. Data were entered in Epi Data version 4.6 and analyzed using SPSS version 25 software. A bivariable and multivariable logistic regression model was used. Odds ratio with 95% confidence interval and p-value ≤ 0.05 declared statistical significance association.A total of 636 pregnant women were included in the analysis. Accordingly, pregnant women`s knowledge of birth defects was found to be 49.2% (95% CI 45.4-53.1). Age group < 25 years (AOR=0.16, 95% CI 0.04, 0.61), urban residence (AOR=6.06, 95% CI 2.17, 16.94), antenatal care booked before 20 weeks of gestational age (AOR=3.42, 95% CI 1.37, 8.54), and ever heard on birth defects (AOR=5.00, 95%CI 1.87, 13.43) were significantly associated factors with pregnant women's knowledge of birth defects.Approximately half of the pregnant mothers were aware of birth defects. Addressing prepregnancy and pregnancy health information and education particularly on the prevention of birth defects is recommended.